Предмет: Алгебра, автор: DaRiA555S

Решить любые три уравнения

Приложения:

Ответы

Автор ответа: alma86
2

2 - 3(2x + 2) = 5 - 4x  \\ 2 - 6x - 6 = 5 - 4x \\  - 6x + 4x = 5 - 2 + 6 \\  - 2x = 9 \\ x =  9 \div 2 \\ x = - 4.5 \\ \\ 5 - 2x = 11 - 7(x + 2) \\ 5 - 2x = 11 - 7x - 14 \\  - 2x + 7x = 11 - 14 - 5 \\ 5x =  -8 \\ x =  -  \frac{8}{5}  =  - 1.6\\  \\ 3x  + 5 + (x + 5) = (1 - x) + 4 \\ 3x + 5 + x + 5 = 1 - x + 4 \\ 5x =  - 5  \\  x =  - 1 \\
Похожие вопросы
Предмет: Биология, автор: Алёнкашестиклассница